Analisis Rasio Aktivitas dan Rasio Profitabilitas untuk Menilai Kinerja Keuangan pada PT.AKR Corporindo Tbk Padatahun 2018-2022 - Karmelita Romadona; Rola Manjaleni (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Financial performance appraisal is an integral part of financial management that cannot be separated. The financial performance of a company is an important indicator in decision making for stakeholders, especially investors. This study aims to evaluate the financial performance of PT AKR Corporindo Tbk. during the period 2018 - 2022 using a number of financial ratios, such as receivables turnover, working capital turnover, fixed asset turnover, total asset turnover, return on investment, gross profit margin, and net profit margin. The research method used is quantitative descriptive with purposive area location selection and data collection through literature studies. The results showed that the average financial performance of PT AKR Corporindo Tbk during the period showed that receivables turnover, working capital turnover, fixed asset turnover, and total asset turnover were in the poor category. However, profitability ratios such as net profit margin, return on equity, and gross profit margin are included in the good category. Indicators of activity ratios and profitability that have not reached the standard can be improved by reducing costs that can reduce company profits and utilizing available funds for financing strategies that support the company's progress, which in turn can attract investors and potential investors.